1992
DOI: 10.1002/ijc.2910520402
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and breast‐cancer risk

Abstract: Life-style has a major influence on the incidence of breast cancer. To evaluate the effects of life-style related metabolic-endocrine factors on breast cancer risk we conducted a case-control study comparing 223 women aged 38 to 75 years presenting with operable (stage I or II) breast cancer and 441 women of the same age having no breast cancer, who participated in a population-based breast cancer screening program. Women reporting diabetes mellitus were excluded. Sera from 110 women of the same age group pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
189
4
4

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(202 citation statements)
references
References 31 publications
5
189
4
4
Order By: Relevance
“…The odds ratio between the highest and lowest quintile of insulin levels was 2.83 (95% CI ¼ 1.22 -6.58) after adjusting for dietary and other risk factors such as obesity. Another study showed that serum C-peptide levels, a measure of insulin secretion, were significantly increased in 223 cases with stage I and II breast cancer (38 -75 y) compared to 441 age-matched controls (RR ¼ 2.9, 95% CI ¼ 1.7 -5.1, highest vs lowest quartile, C-peptide difference of 1.7 mg=l ;Bruning et al, 1992). These results were independent of adiposity and body fat distribution.…”
Section: Breast Cancermentioning
confidence: 95%
See 1 more Smart Citation
“…The odds ratio between the highest and lowest quintile of insulin levels was 2.83 (95% CI ¼ 1.22 -6.58) after adjusting for dietary and other risk factors such as obesity. Another study showed that serum C-peptide levels, a measure of insulin secretion, were significantly increased in 223 cases with stage I and II breast cancer (38 -75 y) compared to 441 age-matched controls (RR ¼ 2.9, 95% CI ¼ 1.7 -5.1, highest vs lowest quartile, C-peptide difference of 1.7 mg=l ;Bruning et al, 1992). These results were independent of adiposity and body fat distribution.…”
Section: Breast Cancermentioning
confidence: 95%
“…McKeown-Eyssen (1994) and Giovannucci (1995) hypothesized that hyperinsulinemia=insulin resistance may promote colorectal cancer and possibly other types of cancers related to Western lifestyle (Bruning et al, 1992). High intakes of energy and refined carbohydrates, low intake of vegetables, fruit and dietary fiber, lack of physical activity, obesity, diabetes, hyperinsulinemia and high levels of insulin-like growth factors (IGFs) have been implicated in the etiology of various types of cancer (Giovannucci, 1999).…”
Section: Glycemic Index and Cancermentioning
confidence: 99%
“…Case-control studies have shown hyperinsulinaemia to be a risk marker for breast cancer (Berstein et al, 1985;Bruning et al, 1992;Yoshikawa et al, 1994;Tekden et al, 1996). Insulin itself is an important growth factor influencing mammary cancer cells in vitro but its major growth-promoting effect in vivo is likely to be through IGF1 and IGF1 1.…”
Section: Igf1 Hyperinsulinaemia and Breast Cancermentioning
confidence: 99%
“…These include cancers of the endometrium, bowel, lung and stomach (Berstein et al, 1985;Copeland et al, 1987;Heslin et al, 1992;Rutanen et al, 1993;Vishnevsky et al, 1993;Yoshikawa et al, 1994;Yam et al, 1994;Giovanucci, 1995). The association of hyperinsulinaemia with early stage colorectal cancer (Copeland et al, 1987) and early stage breast cancer (Bruning et al, 1992) suggests that it precedes clinical manifestation of the cancer and does not result from cachexia.…”
Section: Igf1 Hyperinsulinaemia and Breast Cancermentioning
confidence: 99%
“…Additional hormonal changes that might also contribute to reduce breast cancer risk are the reduction in insulin, and increases in IGFBP-1 and -2 (which may reduce IGF-I bioactivity within the breast). Besides estradiol, IGF-I and insulin may exert direct growth-promoting effects on breast epithelium (Kaaks, 1996;Papa & Belfiore, 1996;Chappell et al, 2001;Lai et al, 2001), and there is some evidence that both elevated circulating insulin (Bruning et al, 1992;Del Giudice et al, 1998;Yang et al, 2001) and elevated circulating free IGF-I (Li et al, 2001) may increase breast cancer risk, and worsen breast cancer prognosis (survival time) (Goodwin et al, 2002). An estimation of the breast cancer fraction that might be prevented with the type of diet examined in our study remains difficult, however, as favourable alterations in endogenous hormone levels relatively late in life may not have the same effect on risk as having had a more favourable hormone level lifetime.…”
mentioning
confidence: 99%